Identification of upregulated exosomal miRNAs between A2780 and A2780/DDP human ovarian cancer cells by high-throughput sequencing - Huihui Wang; Li Liu; Qinying Liu; Jianfeng Zheng; Qiuhong Zheng; Yuwei Chen; Hongmei Xia; Qiaoling Wu; Yang Sun (BMC, 2023)
Abstract Exosomal miRNAs are known to play important roles in ovarian cancer and chemotherapeutic resistance. However, a systematic evaluation of characteristics of exosomal miRNAs involved in cisplatin resistance in ovarian cancer remains totally unclear. Exosomes (Exo-A2780, Exo-A2780/DDP) were extracted from cisplatin-sensitive cells (A2780) and cisplatin-resistant cells (A2780/DDP). Differential exosomal miRNA expression profiles were found by high-throughput sequencing (HTS). Target genes of the exo-miRNAs were predicted by using two online databases to increase the prediction accuracy. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were utilized to find biological relationships with chemoresistance. RT‒qPCR of three exosomal miRNAs was performed, and a protein‒protein interaction (PPI) network was established to identify the hub genes. The GDSC database was used to prove the association between hsa-miR-675-3p expression and the IC50 value. An integrated miRNA-mRNA network was constructed to predict miRNA-mRNA associations. The connection between hsa-miR-675-3p and ovarian cancer was discovered by immune microenvironment analyses. The upregulated exosomal miRNAs could regulate gene targets through signalling pathways such as the Ras, PI3K/Akt, Wnt, and ErbB pathways. GO and KEGG analyses indicated that the target genes were involved in protein binding, transcription regulator activity and DNA binding. The RT‒qPCR results were consistent with the HTS data, and the results of PPI network analysis suggested that FMR1 and CD86 were the hub genes. GDSC database analysis and construction of the integrated miRNA-mRNA network suggested that hsa-miR-675-3p was associated with drug resistance. Immune microenvironment analyses showed that hsa-miR-675-3p was crucial in ovarian cancer. The study suggested that exosomal hsa-miR-675-3p is a potential target for treating ovarian cancer and overcoming cisplatin resistance.